Review of the Fund's Strategy on Overdue Financial Obligations. (Policy Papers; Policy Paper, 2018)
This paper reviews progress under the Fund's strengthened cooperative strategy on overdue financial obligations. The level of overdue obligations to the Fund declined and their structure has remained broadly unchanged since the last review. Total overdue obligations to the Fund at end-June 2017 amounted to SDR 1,205.7 million, a decline of about SDR 100 million from the end-June 2012 level, when the strategy was reviewed last. All overdue obligations to the Fund at end-June 2017 were due to two protracted overdue obligations cases. Sudan accounts for the bulk of the overdue obligations to the Fund (80 percent), and Somalia for the remainder. Zimbabwe, which was in protracted overdue obligations to the PRGT at the time of the last Review, settled its overdue obligations to the PRGT on October 20, 2016.